Challenges and Solutions of Mal Zakat Management: A Case Study of Public Awareness and Trust in UPZ in Rimbo Bujang District - Sifa, Nikmatus; H. Husin Bafadhal; Herri Novealdi; Mahmudi; Angga Bayu Pratama (NALAR FIQH: Jurnal Hukum Islam, 2024)
Zakat has a strategic role in reducing social inequality and improving the welfare of Muslims, but its implementation still faces challenges, especially in the management of mal zakat through official institutions such as the Zakat Collection Unit (UPZ). In Rimbo Bujang Sub-district, the low level of public awareness and trust towards UPZ are the main obstacles in optimizing the management of mal zakat. The lack of zakat mal literacy and lack of innovative education create a gap between zakat obligation and its implementation in the community. This research uses a qualitative approach with descriptive method, relying on in-depth interviews, observation, and document analysis to understand this phenomenon in depth. The results show that the low awareness of zakat mal is caused by the lack of understanding of the zakat mechanism through UPZ and ignorance of its benefits, while the level of public trust in zakat institutions is still low due to the lack of transparency and accountability. Nevertheless, education through religious activities such as tausiyah and leaflet distribution has the potential to improve zakat literacy. This study emphasizes the importance of collaboration between UPZ, religious leaders, and the government in strengthening zakat education regulations and innovations, as well as the use of digital technology to expand the scope of zakat literacy. The findings provide theoretical contributions in zakat literature and offer practical solutions for more effective, inclusive, and transparent zakat management.